MENAKAR URGENSI PENGATURAN PELAKSANAAN DAN PEMBATALAN PUTUSAN BADAN ARBITRASE SYARIAH NASIONAL (BASYARNAS) - Bhismoadi Tri Wahyu Faizal (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2019)
The National Sharia Arbitration Board (BASYARNAS) is a sharia economic dispute resolution institution under the auspices of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Regarding the execution of decisions issued by BASYARNAS against parties who do not voluntarily carry out BASYARNAS decisions, there have been many changes, due to the provisions in Law Number 30 of 1999 which delegated the authority to execute BASYARNAS decisions to district courts even though the decisions were related to sharia economic disputes that should have been under the jurisdiction of the Religious Courts. however, there have been several attempts to restore the authority of the Religious Courts as the only judicial institution authorized as executor of BASYARNAS decisions, including the issuance of the Supreme Court Circular Letter (SEMA) Number 8 of 2008 concerning the Execution of BASYARNAS Decisions. However, the implementation of the SEMA did not last long, because in 2010 the Supreme Court again issued Circular Letter No. 8 of 2010 concerning the Affirmation of the invalidity of SEMA No. 8 of 2008 concerning the Execution of Decisions of the Syrian Arbitration Board. After going through a long gap, in 2014 the Supreme Court Regulation Number 14 of 2016 was issued concerning Procedures for Settlement of Sharia Economic Cases. This PERMA gives full power to the Religious Courts as the authorized institution as the executor of BASYARNAS decisions.